2017
DOI: 10.1590/1678-4324-2017160304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrients on total lipid content and fatty acids profile of Scenedesmus obliquus

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
16
0
2
Order By: Relevance
“…In terms of the biodiesel profile, A. obliquus produced fatty acids similar to other studies (Menezes et al 2013;Soares et al 2014). The total content of saturated fatty acids (RSFA) was lower than that of unsaturated fatty acids (RUFA), which is common in microalgae, as evidenced by Darki et al (2017) in S. obliquus which presented 25.9% of SFA and 74.1% of UFA. Duong et al (2015) recorded 29.7 and 31.4% of SFA and 70.3 and 68.6% of UFA in Scenedesmus sp.…”
Section: Discussionsupporting
confidence: 81%
“…In terms of the biodiesel profile, A. obliquus produced fatty acids similar to other studies (Menezes et al 2013;Soares et al 2014). The total content of saturated fatty acids (RSFA) was lower than that of unsaturated fatty acids (RUFA), which is common in microalgae, as evidenced by Darki et al (2017) in S. obliquus which presented 25.9% of SFA and 74.1% of UFA. Duong et al (2015) recorded 29.7 and 31.4% of SFA and 70.3 and 68.6% of UFA in Scenedesmus sp.…”
Section: Discussionsupporting
confidence: 81%
“…FAMEs quantification and characterization data in this study showed that S. subspicatus cells responded to infochemicals with an increase in the overall amount of intracellular fatty acids produced and with a redistribution of their composition, with varying lengths of acyl chains and different degrees of saturation (Figures 8A,B). The composition of fatty acids is reported to change with changing environmental conditions to allow algal cells to cope with varying circumstances or triggering defense responses (Wacker et al, 2016;Darki et al, 2017), with their function being determined by length, position, and saturation level of their acyl chain(s) (Walley et al, 2013). Although small, the presence of fatty acids in the sEPS matrix of S. subspicatus cells exposed to Daphnia infochemicals was a meaningful indicator of an investment of the algal cells into the production and release of defense compounds.…”
Section: +20 H Exposure -The Acclimation Phasementioning
confidence: 99%
“…High lipid storage under stress strategies is measured in other microalgae species, such as in Chlorella vulgaris 15 , Scenedesmus sp. 31 and Scenedesmus obliquus 32 . However, high lipid storage alone does not capture the overall illustration of the ability of microalgae to be further applied toward biofuel production.…”
Section: Discussionmentioning
confidence: 99%
“…This adaptation is versatile since microalgae are able to adapt to different environments in a short range of time. Versatility is easily observed in species that occupy the lower clades of taxonomy hierarchy, such as Scenedesmus obliquus (considered as intermediate stage in the evolution) which is able to change its normal partitioning from producing high MUFA under Guillard medium to high PUFA in Tamiya medium culture 32 . Interestingly, M. gracile SE-MC4 was able to maintain its C16:0 and C18:1 lipids, making the two major fatty acid composition without altering high lipid partition even under NS culture condition (Figs.…”
Section: Discussionmentioning
confidence: 99%